Improving Community Health Services at Bumi Ayu Community Health Center - Lilis Whyuni; Dewi Jannah; Erika Yusmaini; Wagimin Wagimin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Community health centers (Puskesmas) play a strategic role as primary health care facilities in improving public health status. However, Puskesmas Bumi Ayu still faces several challenges, including limited human resources, inadequate facilities, and suboptimal community participation in supporting health services. This Community Service Program (PKM) aims to enhance the quality of community health services through a community organizing approach that actively involves health workers and service users. The methods employed include health education, interactive discussions, and participatory monitoring and evaluation conducted at Puskesmas Bumi Ayu, Dumai Selatan District. The results indicate an improvement in the understanding of health workers and the community regarding patient-oriented service quality, optimization of available resources, and strengthened collaboration among the health center, local government, and the community. Furthermore, the program fostered collective awareness, positive behavioral changes, and the emergence of local change agents supporting community-based health services. Overall, this PKM contributes to the development of more responsive, inclusive, and sustainable primary health care services in the working area of Puskesmas Bumi Ayu